2018
DOI: 10.1097/01.aoa.0000547304.03058.d8
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic Versus Conventional Lumbar Puncture Needles: A Systematic Review and Meta-Analysis

Abstract: (Lancet. 2018;391:1197–204) Among patients who undergo lumbar puncture, up to 35% return to the hospital with a postdural puncture headache, which is caused by continuing leakage of the cerebrospinal fluid (CSF) from the dural defect created by the spinal needle. Conventional needles are most frequently used in clinical practice by nonanesthesiologists and have a sharp slanted tip designed to cut through the dura with a distal opening for injection of drugs or collection of CSF. As these needles cut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
2
12
0
3
Order By: Relevance
“…dLP is generally safe, but a common complication is postdural puncture headache (PDPH), first described in 1898. (Bier, 1899) Several studies comparing incidence of PDPH when using atraumatic and traumatic needles (Arevalo-Rodriguez et al, 2017;Nath et al, 2018) have confirmed a clear benefit of the atraumatic needle. Other benefits reported with using atraumatic needles are reduced need for epidural blood patch and treatment with intravenous fluids and analgesics.…”
Section: Introductionmentioning
confidence: 99%
“…dLP is generally safe, but a common complication is postdural puncture headache (PDPH), first described in 1898. (Bier, 1899) Several studies comparing incidence of PDPH when using atraumatic and traumatic needles (Arevalo-Rodriguez et al, 2017;Nath et al, 2018) have confirmed a clear benefit of the atraumatic needle. Other benefits reported with using atraumatic needles are reduced need for epidural blood patch and treatment with intravenous fluids and analgesics.…”
Section: Introductionmentioning
confidence: 99%
“…This number corresponds relative tightly with a recent meta-analysis including over 30.000 adult patients undergoing LP for all indications, where PDPH occurred in 11.0% after LP with traumatic needles. 21 Most important for interpretation, our data also reflect occurrence of PDPH after LP with exclusively traumatic needles. It has been shown that the risk of PDPH can be significantly reduced when atraumatic needles are used instead of traumatic needles.…”
Section: Discussionmentioning
confidence: 56%
“…It has been shown that the risk of PDPH can be significantly reduced when atraumatic needles are used instead of traumatic needles. 11,21 We were not able to identify significant risk factors for occurrence of PDPH in our cohorts of SMA patients and paediatric non-SMA patients. However, we saw a trend towards lower PDPH occurrence in our cohort of SMA patients undergoing therapeutic LPs, when compared to diagnostic LPs in the general paediatric cohort.…”
Section: Discussionmentioning
confidence: 78%
“…Galvos skausmas yra viena dažniausių juosmeninės punkcijos komplikacijų, kurią patiria iki 11 proc. pacientų (33). Jis lokalizuojasi kaktoje arba pakaušyje ir gali trukti iki 2 sav.…”
unclassified
“…Nugaros skausmu po juosmeninės punkcijos skundžiasi trečdalis pacientų. Jis dažniausiai tęsiasi kelias dienas ir praeina savaime (33).…”
unclassified